Post-transcriptional regulation and subcellular localization of G-protein γ7 subunit: implications for striatal function and behavioral responses to cocaine - Pelletier, Oliver B.; Brunori, Gloria; Wang, Yingcai; Robishaw, Janet D. (Frontiers in Neuroanatomy, 2024)
The striatal D1 dopamine receptor (D1R) and A2a adenosine receptor (A2aR) signaling pathways play important roles in drug-related behaviors. These receptors activate the Golf protein comprised of a specific combination of αolfβ2γ7 subunits. During assembly, the γ7 subunit sets the cellular level of the Golf protein. In turn, the amount of Golf protein determines the collective output from both D1R and A2aR signaling pathways. This study shows the Gng7 gene encodes multiple γ7 transcripts differing only in their non-coding regions. In striatum, Transcript 1 is the predominant isoform. Preferentially expressed in the neuropil, Transcript 1 is localized in dendrites where it undergoes post-transcriptional regulation mediated by regulatory elements in its 3' untranslated region that contribute to translational suppression of the γ7 protein. Earlier studies on gene-targeted mice demonstrated loss of γ7 protein disrupts assembly of the Golf protein. In the current study, morphological analysis reveals the loss of the Golf protein is associated with altered dendritic morphology of medium spiny neurons. Finally, behavioral Formatted: Subscript analysis of conditional knockout mice with cell-specific deletion of the γ7 protein in distinct populations of medium spiny neurons reveals differential roles of the Golf protein in mediating behavioral responses to cocaine. Altogether, these findings provide a better understanding of the regulation of γ7 protein expression, its impact on Golf function, and point to a new potential target and mechanisms for treating addiction and related disorders.